TINJAUAN HUKUM ISLAM TERHADAP PERAN GANDA PEREMPUAN SEBAGAI ISTRI DAN PENCARI NAFKAH KELUARGA ( STUDI KASUS DI KELURAHAN CIPTO MULYO KECAMATAN SUKUN KOTA MALANG) - A. Ridho Maulana Aziz; Humaidi Kaha; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
The dual role of a career woman is a woman who is involved in professional work activities. Generally, careers are pursued by women outside the home. So that career women are classified as those who take part in the public sector. But in the case of career women in Cipto Mulyo Village, Sukun District, Malang City. some work outside the home and some work from home. A career woman who has the obligation to manage the household as well as possible, helps her husband to work for a living because his husband's income cannot be sufficient for the family's economic needs, so they do not pay attention to their obligatory role as housewives as required women may work according to Yusuf Qardawi's theory of Islamic law. The formulation of the problem in this study is: a review of Islamic law on the dual role of women as wives and family breadwinners in Ciptomulyo Village, Sukun District, Malang City? How does Islamic law review the role of career women in educating children in Ciptomulyo Village, Sukun District, Malang City? The type of this research is qualitative research with a descriptive approach while the data collection technique uses observation, interviews and documentation. The analysis used is a deductive method. From this research, it can be concluded that the review of Islamic law regarding the dual role of career women in Ciptomulyo Village, Sukun District, Malang City, that the overall role of career women in improving the family economy and family welfare in Ciptomulyo Village, Sukun District, Malang City has fulfilled According to Yusuf Qaradawi, the conditions for women to work according to Islamic law are lawful work, behaving according to the Shari'a, the work does not make one negligent in being a housewife, and the work does not mix with men. Then in a review of Islamic law regarding the role of career women in educating children in Ciptomulyo Village, Sukun District, Malang City, the role of career women in educating their children is in accordance with Islamic law regarding education for children, namely education about reason, aqidah, morals, worship, and physical.